STABILITY PERFORMANCE OF TOSSA JUTE (CORCHORUS OLITORIUS L.) UNDER WATERLOGGED CONDITION - SONIKA YUMNAM; ASHUTOSH SAWARKAR; S. MUKHERJEE; .K. SARKAR (The Bioscan, 2015)
Genotype x environment interaction for twenty genotypes of tossa jute were studied over four environments for seven different yield and quality attributing traits to identify genotypes with stable performance under waterlogged condition. Genotype x environment interactions were significant for fibre tenacity and fibre fineness indicating substantial variation among genotypes over the environment. High yielding OIN 955 (12.188 g/plant) showed high stability (bi=0.308 and ó2 di=0.388) to waterlogged environment for the character along with average stability for basal diameter (bi=0.801 and ó2 di=0.023). Relatively poor yielder OIN 941 (9.837 g/plant) also showed stability for yield (bi=0.646 and ó2 di=1.305) along with average stability for quality parameters suggesting presence of resistance genes which could be harnessed to enhance genetic potentiality against inundated environment with simultaneous improvement in fibre quality. The genotypes OIN 955 can be recommended for cultivation under waterlogged condition or as donor parents to improve others commercially potent varieties